A Retrospective Observational Study of The Impact of HIV Status on The Outcome of Paediatric Intensive Care Unit Admissions - Whitehead, Kim (University of the Witwatersrand, Johannesburg, 2022)
BACKGROUND: Previously it was thought futile to offer HIV infected children ICU care, however this has changed with the availability of Antiretroviral Therapy (ART). Improved Prevention of Mother to Child Transmission (PMTCT) has led to a larger population of HIV exposed uninfected (HEU) children with unique health risks. Our study looked at how HIV exposure and infection impact presentation and outcomes in PICU in an era of improved access to ART and PMTCT. METHODS: A retrospective analysis of children admitted to PICU at a tertiary/quaternary hospital between 2015 and 2019 was conducted. De-identified data was obtained from an existing database and analysed using SPSS software. Medians and interquartile ranges were used to analyse continuous variables and frequencies and percentages to analyse categorical variables. The sample was then divided into three groups (HIV negative, HEU and HIV infected) and their presentation and outcomes compared using Chi-Squared and Kruskall-Wallis tests with a significance level set at p < 0.05. RESULTS: Our study showed that 16% (109/678) of children admitted to PICU were HEU and 5.2% (35/678) HIV infected. HIV infected children were admitted at a younger age (median two months) and had an increased incidence of lower respiratory tract infections than HIV negative children (p < 0.001). HIV infected children required longer ventilation and admission than HIV negative and HEU children (p < 0.001). HIV infected children had a higher mortality (40%) (p = 0.02) than HIV negative children (mortality 22.7%); when comparing children admitted with a medical diagnosis however the difference in mortality was not statistically significant (p = 0.273). HEU children were admitted at a younger age (median three months) with a higher incidence of lower respiratory tract conditions than HIV negative children (p < 0.001). HEU children had similar outcomes to HIV negative children with no statistically significant difference in duration of ICU stay (p =0.163); ventilation (p = 0.443) or mortality (p=0.292). CONCLUSION: HIV infected children presented with more severe disease requiring longer ventilation and admission. HEU had similar outcomes to HIV negative children.
A research report submitted as part of the requirements for the degree of Master of Medicine in Paediatrics, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022
Keywords: Human Immunodeficiency Virus; Paediatric Intensive Care Unit; Outcomes; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education